Crystal structure of 5-(2,2-difluoropropyl)-5-methyl-6-oxo-5,6-dihydrobenzo[4,5]imidazo[2,1-a]isoquinoline-3-carbonitrile, C20H15F2N3O - Liu Hongqian; Liu Hongmei; Fu Shaoyan; Tang Wenqiang (Zeitschrift für Kristallographie - New Crystal Structures)
C20H15F2N3O, monoclinic, P21/c (no. 14), a = 7.2737(2) Å, b = 9.5461(3) Å, c = 24.0298(8) Å, β = 91.5320(10)°, V = 1,667.92(9) Å3, Z = 4, Rgt(F) = 0.0459, wRref(F2) = 0.1164, T = 150 K.